Collapse load analysis for circumferentially cracked cylinder subjected to combined torsion and bending moments - Sutham Arun (2018)
© The Authors, published by EDP Sciences, 2018. Cylinder is one of the most commonly used components which has a risk of having circumferential cracks, especially in the welding zone. When cracks are discovered, it is necessary to perform the failure strength assessment of cracked cylinder and the limit load play an important part as the input of the assessment. At present, the limit load solution for circumferential cracked cylinder under combined bending and torsion can be estimated by using the methods of equivalent moment or biaxial failure parameter. However, these methods still have some limitations. The main aim of this paper is to propose the alternative method for predicting the failure moment of circumferential cracked cylinder under combined bending and torsion. The method used in this paper is based on the modification of biaxial failure parameter and the data from finite element analysis. Details of this method is presented in this paper.